Qualities and attributes of a safe practitioner: identification of safety skills in healthcare. Issue 6 (5th January 2011) - Long, S; Arora, S; Moorthy, K; Sevdalis, N; Vincent, C
Abstract : Objectives: (1) To identify a range of safety skills (attributes of a safe practitioner) relevant across clinical specialities. 2) To obtain the views of clinicians regarding their importance and trainability. Design: We used a survey and focus group of 10 patient safety experts to extract a list of safety skills. 50 experienced clinicians rated the skills in terms of importance and trainability in an electronic questionnaire. Setting: A Clinical Safety Research Unit and its associated NHS Trust, within an Academic Health Science Centre. Results: 73 skills, in 18 broad categories, were identified from the focus group and survey. The majority of clinicians felt the skills were important (most important: technical skills (98%), crisis management (98%), honesty (97.5%); least important: open-mindedness (82%), patient awareness/empathy (81.7%), humility (81.2%)). There was less agreement about trainability (16/18 categories were felt to be trainable; most trainable: technical skills (98%), anticipation/preparedness (84%), organisational skills/efficiency (83%); least trainable: conscientiousness (56%), humility (40%), open-mindedness (30%)). More surgeons than physicians felt that team awareness and crisis management skills were trainable (p=0.0099, p=0.025, respectively). Conclusions: We have identified a preliminary set of safety skills, which with further refinement could form the template for the development of a formal taxonomy of the qualities and attributes of the safe practitioner. Experts and practitioners agree about the importance of the individual skills. The fact that the majority of these were felt by experienced cross-speciality clinicians to be trainable is encouraging in terms of the possibility of developing generic safety curricula.